Taoist ritual and popular cults of Southeast China - Dean, Kenneth, 1956- (Princeton University Press, 1993)
Most commentators imagine contemporary China to be monolithic, atheistic, and materialist, and wholly divorced from its earlier customs, but Kenneth Dean combines evidence from historical texts and extensive fieldwork to reveal an entirely different picture. Since 1979, when the Chinese government relaxed some of its most stringent controls on religion, villagers in the isolated areas of Southeast China have maintained an "underground" effort to restore traditional rituals and local cults.Originally published in 1993.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.